Ganti Rugi Hak Milik Atas Tanah Oleh PT.PLN (Persero) - Sandi Yaning Pattimura; Merry Tjoanda; La Ode Angga (Faculty of Law Universitas Pattimura, 2023)
ABSTRACT: Development requires land whose acquisition is carried out by prioritizing the principles contained in the 1945 Constitution of the Republic of Indonesia (UUD NRI 1945) and national land law. The establishment of electricity networks is also included in land acquisition. But in fact PT. PLTD Poka Ambon city has used the land of HH heirs covering an area of 2000 meters without any deliberation or permission from the landowner located in Poka for approximately 32 years in 1991 without any compensation. The type of research conducted in this writing is normative juridical legal research which is analytically descriptive. Normative legal research is a form of legal writing based on the characteristics of normative legal science. The first thing to do in normative research based on primary and secondary legal materials is an inventory of regulations related to civil law. The purpose of this research is to find a clear legal basis for placing this problem in the perspective of National Agrarian law The purpose of this research is to find a clear legal basis for placing this problem in the perspective of National Agrarian law. Based on the description of the results and discussion, the form of responsibility of PT PLN (Persero) in providing compensation related to the use of land exceeding the limit unilaterally can be seen in Law No. 30 of 2009 concerning Electricity. as referred to in Article 27 is carried out by providing compensation for land rights or compensation to holders of rights to land, buildings and plants in accordance with the provisions of laws and regulations. The form and amount of such compensation should be designed in such a way that the people affected by the development activities do not experience a setback both in terms of social and economic.